1978
DOI: 10.1073/pnas.75.1.285
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Rous sarcoma viral RNA translation by a specific oligodeoxyribonucleotide.

Abstract: A tridecamer oligodeoxynucleotide, d(A-A-T-G-G-T-A-A-A-A-T-G-G), which is complementary to reiterated 3'- and 5'-terminal nucleotides of Rous sarcoma virus 35S RNA, is an efficient inhibitor of the translation of proteins specified by the viral RNA in the wheat embryo cell-free system. The inhibition specificity for oncornavirus RNA is greater than for rabbit reticulocyte mRNA or brome mosaic virus RNA. Other oligodeoxynucleotides of similar size have little or no specific effect on the RNA-directed translatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
365
0
7

Year Published

1987
1987
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 775 publications
(381 citation statements)
references
References 23 publications
1
365
0
7
Order By: Relevance
“…[30][31][32][33] The possible mechanisms by which antisense molecules result in decreased protein expression include the modulation of protein translation by disrupting ribosome assembly, RNase H mediated cleavage of targeted mRNA, and pre-translational modification of splicing. 30,34 Antisense molecules were described as long ago as 1978, 35 but adjustment of their structures has led to improvements in pharmacokinetics and pharmacodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33] The possible mechanisms by which antisense molecules result in decreased protein expression include the modulation of protein translation by disrupting ribosome assembly, RNase H mediated cleavage of targeted mRNA, and pre-translational modification of splicing. 30,34 Antisense molecules were described as long ago as 1978, 35 but adjustment of their structures has led to improvements in pharmacokinetics and pharmacodynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments indicated that the dissociation mechanism of RNA is not influenced by the nucleobase, thus, supporting a mechanism where dissociation is initiated by formation of an intramolecular cyclic transition state with the 2=-hydroxyl proton bridged to the 5=-phosphate oxygen. A ntisense oligonucleotides are nucleic acids of about 12 to 20 nucleobases, which are designed to hybridize to a complementary messenger RNA (mRNA) sequence, thus, inhibiting gene expression [1][2][3]. Therefore, they are of great interest in human cancer therapy and for diagnostic applications.…”
mentioning
confidence: 99%
“…With a single antisense species 80 to 90% inhibition has been achieved (Izant and Weintraub, 1985;Green et al, 1986): it seems likely that the use of two or more antisense RNAs would give higher levels of inhibition. The effectiveness of the process has been demonstrated in a number of applications including the inhibition of devlopmental genes (Rosenberg et al, 1985;Crowley et al, 1985), viral genes (Izant and Weintraub, 1984) and of Rous sarcoma infection in vitro (Stephenson and Zamecnik, 1978;Zamecnik and Stephenson, 1978).…”
Section: Genes For Insertionmentioning
confidence: 99%